Analysis of Drill Spasing Based on Coal Thickness and Quality Variability for Coal Resouces in Musibanyuasin - Hadi Kurniawan; Setyo Pambudi; Hita Pandita (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Drill spacing determination is one of the important aspects of coal exploration planning because it directly affects geological confidence, resource estimation, and exploration cost efficiency. This study was conducted on Seam F of the Muara Enim Formation in Musi Banyuasin Regency, South Sumatra. The objective of this study is to evaluate the quantitative variability of coal thickness and quality and to determine the optimum drill spacing as a basis for future exploration planning.  The analyzed parameters include coal thickness, ash content, total sulfur, and calorific value. The dataset consists of 115 collar points for coal thickness and 71 collar points for coal quality, with an average existing drill spacing of approximately 422 m. The methods used in this study include descriptive statistics, omnidirectional variogram analysis, global estimation variance (GEV), and relative error (RE). Drill spacing simulation was carried out using spacing scenarios ranging from 100 m to 3000 m to evaluate changes in estimation uncertainty with increasing drill hole distance. The results show that Seam F has an average thickness of approximately 3.19 m with a coefficient of variation (CoV) of 0.06, indicating low thickness variability. Coal quality parameters also show relatively low variability, with CoV values of 0.04 for ash, 0.05 for total sulfur, and 0.01 for calorific value. However, geostatistical analysis indicates that each parameter has different spatial continuity characteristics. Total sulfur has a nugget ratio of 11.7%, indicating relatively good spatial continuity, whereas calorific value has a nugget ratio of 60.8%, indicating stronger local variability. The GEV and RE analyses show that estimation uncertainty increases as drill spacing becomes wider. Based on RE thresholds for coal resource classification, the recommended optimum drill spacing for Seam F is 550 m for measured resources, 825 m for indicated resources, and 1,650 m for inferred resources. This study shows that the integration of descriptive statistics, variogram analysis, GEV, and RE can provide a quantitative and objective basis for determining drill spacing in future coal exploration planning.